If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8b = 2b Solving 8b = 2b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-2b' to each side of the equation. 8b + -2b = 2b + -2b Combine like terms: 8b + -2b = 6b 6b = 2b + -2b Combine like terms: 2b + -2b = 0 6b = 0 Divide each side by '6'. b = 0 Simplifying b = 0
| 64c^2-16=0 | | 5(2x-4)=0 | | -8(x+3)+2x+5=7x+9 | | 3+x+27=180 | | (2x+3)(4x-4)= | | [9(p+4)-18]-[2(p-4)+1]= | | 9(2k+3)+2=11(k-.5) | | .4x+7=.6x | | 2c-7=18 | | .8x-.2y-.1x-1.2y=.7 | | y-3/3-y-2/2=-1 | | 18/65=x/35 | | 9(q+9)= | | 13(4x+4)=3(5x+6) | | 5x=23+y | | 100(29)=10(29) | | 2xsquared-x=3 | | Y/9-6=-14 | | 5x+9=9+2x | | 8x-11/7=-5 | | z/15-6=14 | | 3x-12=-4x+32 | | v=(p*q)-((p*q)/100*5)-p | | -2=6/8 | | 3(16-4y)4y=8 | | 8-9s+s^2= | | 1015=2x+5 | | 4-3d=8 | | -9x-6=-3(3x+2) | | d=2m+3m | | 4x+5x(-5)=21 | | 3(2n-5)=-7-2 |